A nano-preparation approach to enable the delivery of daphnoretin to potentiate the therapeutical efficacy in hepatocellular cancer - Zhu, Guanglin; Wang, Bing; Feng, Guo; Zhou, Zhirong; Li, Wei; Liu, Wen; Su, Hongmei; Wang, Wenjing; Wang, Tiejie; Yu, Xie-an (Frontiers in Pharmacology, 2022)
Daphnoretin (DAP), isolated from a traditional Chinese medicine Wikstroemia indica (Linn. C. A. Meyer), could induce apoptosis of hepatocellular cancer (HCC) and inhibit tumor growth. However, the application of DAP in cancer therapies was hampered because to its poor solubility. Herein, this study aimed to design an approach of double-targeted nano-preparation to enable the delivery of DAP to potentiate the therapeutical efficacy in liver cancer via glycyrrhetinic acid-polyethylene glycol-block-poly (D,L-lactic acid)/polyethylene glycol-block-poly (D,L-lactic acid)-DAP (GPP/PP-DAP). In particular, the purity of separated DAP was up to 98.12% for preparation research. GPP/PP-DAP was successfully prepared by the thin-film hydration method. Subsequently, the GPP/PP-DAP was optimized by univariate analysis and the response surface methodology, producing a stable and systemically injectable nano-preparation. Impressively, on the one hand, cytotoxicity studies showed that the IC50 of the GPP/PP-DAP was lower than that of free DAP. On the other hand, the GPP/PP-DAP was more likely to be endocytosed by HepG2 cells and targeted to the liver with orthotopic tumors, potentiating the therapeutical efficacy in HCC. Collectively, both in vitro and in vivo results indicated the excellent tumor inhibition and liver targeting of GPP/PP-DAP, suggesting the nano-preparation could serve as a potential drug delivery system for natural ingredients with anti-hepatoma activity to lay the theoretical foundation for clinical application.